A novel Approach to Compute Steiner point in Graph: Application for Network Design - Chandak, MB; Bhalotia, S; Agrawal, SC (International Journal of Computer Sciences and Engineering, 2025)
A Graph has two main components: Vertices and Edges. The vertices are connected using edges. There are two types of graphs, directed and undirected. The major application of graph is representing network on paper. The cost involved in converting paper based network to actual cable based network is majorly controlled by cables required for connection. The cost can be reduced if the length of cable can be reduced. The paper describes the methodology to compute Steiner point. Using Steiner point, it is possible to modify the position of vertices, so as to reduce the cable length, keeping the vertex connectivity intact. The paper describes implementation of Steiner point on graph with number of vertices as 3, 4, 5 and 6. The presented work can be extended for graph with any number of vertices. It is an optimization approach to reduce the cable size and cost of network implementation.